2020
DOI: 10.1186/s42269-020-00350-8
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of the Egyptian isolates “extensively drug-resistant Pseudomonas aeruginosa” and detection of their metallo-β-lactamases encoding genes

Abstract: Background: Carbapenem antibiotics consider the primary treatment choice for serious Pseudomonas aeruginosa infection. Hence, the evolution of carbapenem resistance mediated by acquiring genes encoding class b enzymes is of global concern. The purpose of this article research is to explore the prevalence, drug resistance profiles, and metallo-βlactamases (MβLs) production in extensively drug-resistant carbapenem-resistant P. aeruginosa (XDR-CRPA). Methods: P. aeruginosa isolates were collected and identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
8
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 37 publications
4
8
5
Order By: Relevance
“…Concerning meropenem susceptibility in this study, 35 (44.8%) of isolates were meropenem resistant. In a similar study in Egypt by Basha and coworkers [23], it was reported that 57% of their isolated P. aeurginosa were resistant to meropenem. Also 62% of isolates from health care associated infections at Suez Canal University Hospitals were meropenem resistant Kishk et al [1].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Concerning meropenem susceptibility in this study, 35 (44.8%) of isolates were meropenem resistant. In a similar study in Egypt by Basha and coworkers [23], it was reported that 57% of their isolated P. aeurginosa were resistant to meropenem. Also 62% of isolates from health care associated infections at Suez Canal University Hospitals were meropenem resistant Kishk et al [1].…”
Section: Discussionmentioning
confidence: 79%
“…However, a lower resistance rate was detected by Fotouh et al [21] who reported that (22.2%) of P. aeruginosa isolated from surgical site infection of patients admitted at Zagazig University hospitals were meropenem resistant. High meropenem resistance rate detected might be correlated with the selective pressure from increased use of carbapenems for P. aeurginosa infections [23].…”
Section: Discussionmentioning
confidence: 94%
“…So, the spread of P. aeruginosa with MβL activity could result in a panresistant phenotype, thus resulting in further limitation of therapeutic treatment options for these isolates. 9 In this study, we aimed to evaluate the predominance of aminoglycoside resistance among MDR and XDR P. aeruginosa isolates, and to detect the main mechanisms of resistance and the most prevalent aminoglycoside resistance genes. Since carbapenem resistance represents a crucial problem that further limits therapeutic options in these isolates, bla MβL s were also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…So, the spread of P. aeruginosa with MβL activity could result in a pan-resistant phenotype, thus resulting in further limitation of therapeutic treatment options for these isolates. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Figure5Summary of the prevalence (%) of carbapenemase genes in P. aeruginosa. Notes: Data from references37,40,[44][45][46][47]49,51,80,[85][86][87][88][89][90][91][92] . a % of MBL-producing P. aeruginosa; b % of P. aeruginosa isolates resistant to one or more β-lactams; c % of XDR-CRPA; d % of imipenem-resistant P. aeruginosa; e % of carbapenemase genes…”
mentioning
confidence: 99%